Hate speech as a structural phenomenon. Issue 2 (2nd July 2020) - Carlson, Caitlin Ring
ABSTRACT: Hate speech is more than just expression used to malign people based on their fixed identity characteristics. It is a tool deployed by those with various forms of power to maintain their social, political, or economic dominance. It puts its victims in a subordinate position, which makes equality all but impossible. Therefore, we must reconsider the near absolute protection afforded to hate speech under the First Amendment. Americans should utilize existing civil legal remedies to combat hate speech, which only serves to maintain systems of oppression such as white supremacy, gender inequity, and heteronormativity. By opening the door to civil penalties against the subordination caused by hate speech, we pave the way for those seeking equality to achieve it.